Study of Using Vit. C to Reduce the Toxic Immunosuppressive Effect of Aflatoxin in Broilers - Omran, Hassiba A. (The Iraqi Journal of Veterinary Medicine, 2010)
This study was conducted to investigate the adverse effect of aflatoxine contaminated ration on immune response induced by N D vaccine in broilen and the effect of adding vit C in drinking water in reducing the aflatoxine immune supportive effect.A total of 75 day old broiler chicken were divided randomly in to three equal groups , the first group was feed aflatoxine free ration while second and third groups were feed on aflatoxine contaminated ration at 6 day of age, in addition to that the third group have received vit C in a drinking water (125 mg/litter). The birds were immunized twice with ND vaccine at 10, 20 day of age and ELISA test was carried out to estimate the humeral immunity response at 6, 19, 31, days of age.All the groups were challenged with velogenic ND strain (Z 2003). At 32 day of age.The results showed that the first group has high significant antibodies titer reach to 3239±249.3 at 19 days of age and 10186± 845.3 at 31 days of age with significant level p< 0.01 and high protection ratio against challenge (100%) at 32 days of age, while the second group showed a low antibodies titer reach to 2622.6± 27.3 at the 19 days of age and 5712.5± 786.9 at 31 days of age and low protection ratio against challenge (66.67%). the third group showed a high significant antibodies titer reach to 2795± 930.9 at 19 days of age and 7030.1± 246.7 at 31 days of age with significant level p< 0.01 with a protection ratio against challenge 80% at 32 days of age which mean that the third group showed antibodies titer and protection ratio lower than the first group and higher than second group. This study was concluded that giving diets contaminated with aflatoxine cause adverse effects on immune response while the administration of vit C in drinking water improves it .